Sosialisasi Profesi Aktuaris: Referensi Karir Prospektif Yang Menjanjikan bagi Siswa SMA/SMK Wilayah Kota Palangka Raya - Basani, Yuniarta; Ayu, Regina Wahyudyah Sonata; Monita, Dita; Afli, Febrianto; Puspitorini, Mega; Yumia, Mega; Arsana, Mu’afa Purwa; Wilda, Robiatul Witari (Universitas Methodist Indonesia, 2024)
This profession operates in the insurance sector which has risk management expertise and is needed at this time. The method used is outreach to teachers and high school students in Palangka Raya. The socialization of the actuary profession aims to increase knowledge of the actuarial profession and introduce actuaries as a field of study in mathematics study programs so that it becomes an inspiration for choosing a study program when continuing to college. Through this service activity, there is an increase in understanding of the actuarial profession and job opportunities for an actuary by lecturers from the Mathematics Study Program with the team from the Center for Financial Professional Development, Ministry of Finance of the Republic of Indonesia.